Green Marketing a new approach in new wave marketing based on consumers perspective - Mike Steven, Emocling, John Ashley Lopez, Eric John Llovido, Mierell Manalaysay, and Paul Justin Masangkay. 4 0 16; 5 (2016)
u
Thesis: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2